Upaya Guru PAI dalam Meningkatkan Akhlak Mulia Peserta Didik di Masa Pandemi Covid 19 - Muhammad Abdul Khakim (Jurusan Tarbiyah dan Pendidikan, 2021)
Government policy, especially in the field of education, states that in addition to educating the nation's life, educational development is also directed at improving the noble character of students by the demands and needs of development that is cultural, environmental, and religious. extraordinary impact in all fields, including the world of education, especially in Indonesia. The world of education, where previously the learning process was carried out in the classroom and school environment, is now forced to be carried out online. The aspect that is most difficult for students to achieve in online learning is an attitude, both social and spiritual attitudes which are shown by noble character behavior as a result of learning and habits taught in schools. The writing of this article is to identify the difficulty of providing noble moral education to students during the covid 19 pandemic, where the aim is to be able to provide knowledge of PAI teachers' efforts in improving students' noble character even with online learning during the covid 19 pandemics. The results of the discussion explain that PAI teachers must innovate in carrying out online learning by continuing to provide examples, habits, lectures, and prizes or punishments to students packaged in online learning. This will be interesting because learning is not monotonous lectures. Thus, the COVID-19 pandemic condition cannot be used as an excuse for PAI teachers, especially in providing knowledge transfer and printing students with noble character.